Altered placental tryptophan metabolic pathway in human fetal growth restriction. (April 2017) - Murthi, Padma; Wallace, Euan M.; Walker, David W.
Abstract: Introduction: Tryptophan is a substrate for kynurenine pathway metabolism in the placenta. We investigated if kynurenine metabolites change over gestation, if they are different between pregnancies with normal and fetal growth restriction (FGR), and if the oxygen environment modulated kynurenine pathway activity in the human placenta. Methods: Tryptophan, kynurenine, and downstream kynurenine metabolites were determined in maternal venous blood, umbilical cord blood, and placental samples obtained in 1st and 3rd trimester pregnancies including FGR, and in the media of placental explants incubated with 20% or 5–8% O2 for 24, 48 or 72 h. Results: All the major kynurenine metabolites were present in cord blood, and in general were higher than in maternal blood. IDO and TDO mRNA and protein expression, responsible for kynurenine production from tryptophan, were significantly lower in placentas from FGR pregnancies compared with control. Explants prepared from 1st and 3rd trimester placentas actively produced all the major kynurenine pathway metabolites which, together with expression of IDO, TDO, KYN-OHase and 3HAO mRNAs, were significantly lower after 24 h exposure to 5–8% O2 compared to 20% O2 Conclusions: Expression and activity of the kynurenine pathway is present in the placenta from early gestation, and is down-regulated by hypoxia and in FGR pregnancies. Highlights: The human placenta activity converts tryptophan to kynurenine metabolites from early (1st trimester) pregnancy. Enzymes responsible for kynurenine production are significantly lower in placentas from FGR compared with control. Synthesis and release of kynurenine metabolites in placental explants was lower under 5% O2 compared to 20% O2 . Activity of kynurenine pathways enzymes are sensitive to oxygen and conditions that produce FGR.